Nitrogen effect on hydrogen diffusivity and hydrogen embrittlement behavior in austenitic stainless steels. (15th July 2020) - Kim, Kyung-Shik; Kang, Jee-Hyun; Kim, Sung-Joon
Abstract: Hydrogen embrittlement behavior of three austenitic stainless steels with 0.1–0.3 wt% N was investigated by electro-chemical charging of hydrogen. The degradation of tensile properties was alleviated by nitrogen. Hydrogen permeation testing revealed that the increase of nitrogen content decreased the hydrogen diffusivity, and thereby, reduced the depth of hydrogen-affected zones. Intergranular cracks were formed in an early stage of deformation by hydrogen charging and reduced the strain-hardening rate. The cracks propagated further into the grains along martensite/austenite interfaces especially in steels with less nitrogen. Graphical abstract: Image, graphical abstract